A single FTO gene variant rs9939609 is associated with body weight evolution in a multiethnic extremely obese population that underwent bariatric surgery - Rodrigues, Gisele K.; Resende, Cristina M.M.; Durso, Danielle F.; Rodrigues, Lorena A.A.; Silva, José Luiz P.; Reis, Rodrigo C.; Pereira, Solange S.; Ferreira, Daniela C.; Franco, Gloria R.; Alvarez-Leite, Jacqueline (Nutrition, 2015)
The rs9939609 single nucleotide polymorphism (SNP) in the fat mass and obesity-associated (FTO) gene is involved in obesity. Few studies have been conducted on patients who underwent bariatric surgery. The aim of this study was to evaluate the influence of FTO SNPs on body weight, body composition, and weight regain during a 60-mo follow-up period after bariatric surgery. The rs9939609 was genotyped in 146 individuals using a real-time polymerase chain reaction TaqMan assay. Data for lifestyle, comorbidities, body weight, body mass index (BMI), excess weight loss (EWL), and body composition were obtained before and 6, 12, 18, 24, 36, 48, and 60 mo after surgery. Data were analyzed by comparing two groups of patients according to rs9939609 FTO gene polymorphism. Mixed-regression models were constructed to evaluate the dynamics of body weight, BMI, and EWL over time in female patients. No differences were observed between the groups during the first 24 mo after surgery. After 36, 48, and 60 mo, body weight, fat mass, and BMI were higher, whereas fat-free mass and EWL were lower in the FTO-SNP patient group. Weight regain was more frequent and occurred sooner in the FTO-SNP group. There is a different evolution of weight loss in obese carriers of the FTO gene variant rs9939609 after bariatric surgery. However, this pattern was evident at only 2 y postbariatric surgery, inducing a lower proportion of surgery success and a greater and earlier weight regain.
Keywords: Polymorphism; Fat mass and obesity-associated (FTO) gene; Obesity; Bariatric surgery; Weight regain